2019
DOI: 10.3390/cells8050431
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Signaling Pathway in Cancer Targets Photodynamic Therapy In Vitro

Abstract: The Mechanistic or Mammalian Target of Rapamycin (mTOR) is a major signaling pathway in eukaryotic cells belonging to the P13K-related kinase family of the serine/threonine protein kinase. It has been established that mTOR plays a central role in cellular processes and implicated in various cancers, diabetes, and in the aging process with very poor prognosis. Inhibition of the mTOR pathway in the cells may improve the therapeutic index in cancer treatment. Photodynamic therapy (PDT) has been established to sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 132 publications
1
15
0
Order By: Relevance
“…In our phosphoproteomic profile, phosphorylation of heat shock protein HSP 90-alpha (HSP90AA1) at serine 231 was also identified with 11.06 fold-changed upon silencing of ZNF322A, which may contribute to autophagy, however the phosphosite-specific antibody has not yet been established. As previously reported, ZNF322A may act as regulator in gene transcription mediated by the MAPK signaling pathways [60]. Consistent with our findings that siZNF322A upregulated the phosphorylation of HSP27 and MAPKAPK2, participating in p38 MAPK pathway which is responsible for the autophagosome formation.…”
Section: Discussionsupporting
confidence: 93%
“…In our phosphoproteomic profile, phosphorylation of heat shock protein HSP 90-alpha (HSP90AA1) at serine 231 was also identified with 11.06 fold-changed upon silencing of ZNF322A, which may contribute to autophagy, however the phosphosite-specific antibody has not yet been established. As previously reported, ZNF322A may act as regulator in gene transcription mediated by the MAPK signaling pathways [60]. Consistent with our findings that siZNF322A upregulated the phosphorylation of HSP27 and MAPKAPK2, participating in p38 MAPK pathway which is responsible for the autophagosome formation.…”
Section: Discussionsupporting
confidence: 93%
“…The PI3K/AKT pathway is a regulator of aerobic glycolysis and central glucose metabolism 124 . It confer advantages on MDR due to the acidification of the intracellular microenvironment, which may reduce drug absorption and efficiency, and/or an increase in intermediate metabolites 125,126 . Because cell growth depends on the biosynthesis of cellular building blocks produced by metabolic intermediates, it is easy to understand the seemingly contradictory use of this fuel 127 .…”
Section: Bcrpmentioning
confidence: 99%
“…Thus, we found that depletion of linc00342 retarded cell proliferation, accelerated cell apoptosis, and signi cantly reduced migration and invasion ability in KIRC cells. KEGG analysis showed linc00342-related genes were enriched in several important signaling pathways -MAPK, mTOR, insulin, NOD-like receptor, Wnt, and GnRH -that are reported to play key roles in many malignancies [27][28][29][30][31][32]. The effect of these KEGG pathways on the progress of KICC was not explored in our current study.…”
Section: Discussionmentioning
confidence: 70%